An integrated method for color correction based on color constancy for early mural images in Mogao Grottoes - Liu, Zhen; Liu, Yi-Xuan; Gao, Gui-Ai; Kong, Yong; Wu, Bing; Liang, Jin-Xing (Frontiers in Neuroscience, 2022)
Restoring the correct or realistic color of a cultural heritage object is a crucial problem for imaging techniques. Digital images often have undesired color casts due to adverse effects caused by unstable illuminant conditions, vignetting, and color changes due to camera settings. In this work, we present an improved color correction method for color-cast images that makes the color appear more realistic. It is based on a computational model of the human visual system that perceives objects by color constancy theory; it realizes illumination nonuniformity compensation and chromaticity correction for color-cast images by taking into account the color stability of some pigments. This approach has been used to correct the color in Cave 465 of the Mogao Grottoes. The experimental results demonstrate that the proposed method is able to “adaptively correct” color-cast images with widely varying lighting conditions and improve the consistency efficaciously. It can achieve improved consistency in the mean CIEDE2000 color difference compared with the images before correction. This colorimetric correction methodology is sufficiently accurate in color correction implementation for cast images of murals captured in the early years.